Design of Nanostructured Selective Surfaces for Solar to Thermal Energy Conversion. Issue 1709 (19th August 2014) - Gau, Daniel L.; Marotti, Ricardo E.; Davoine, Federico; Amy, Lucía I.; Dalchiele, Enrique A.; Romero, Rocío; Ramos-Barrado, José R.; Leinen, Dietmar; Martín, Francisco; Botasini, Santiago; Méndez, Eduardo; Abal, Gonzalo
ABSTRACT: The solar absorptance αs of nanostructured selective surface (NSS) for solar thermal energy is improved. The NSS are prepared by AC electrochemical impregnation of metal inclusions (MI) into porous anodized aluminum oxide (AAO). The dependence of the NSS performance with composition depth profile and MI is studied by numeric simulations based in a gradient index model and effective medium theory. The results are compared with experimental NSS prepared varying three control parameters and MI (Ni, Cu, Ag). The αs is improved to > 85% (keeping thermal emittance εT relatively low) for Ni MI, mainly by increasing MI content. Increasing AAO thickness or MI molecular weight (for a given experimental composition profile) also improves the performance. For Ag the αs was further improved to 90%.